2006
DOI: 10.1007/978-3-540-35513-7_17
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of m–Stable Sets and in Particular of the Set of Risk Neutral Measures

Abstract: Abstract. The study of dynamic coherent risk measures and risk adjusted values as introduced by Artzner, Delbaen, Eber, Heath and Ku, leads to a property called fork convexity, rectangularity or m-stability. We give necessary and sufficient conditions for a closed convex set of measures to be fork convex. Since the set of martingale measures for price processes is m-stable, this leads to a characterisation of closed convex sets that can be obtained as the set of risk neutral measures in an arbitrage free model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
224
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(230 citation statements)
references
References 13 publications
(39 reference statements)
5
224
0
1
Order By: Relevance
“…The limiting cases γ = 0 and γ = ∞ are defined as [13]. In a continuous time framework, under a filtration for which all martingales are continuous, it is shown that the only law invariant, time consistent, dynamic coherent risk measure (a dynamic convex risk measure, which additionally satisfies ρ t (λX) = λρ t (X) for all λ ∈ (L ∞ t ) + ) is either the negative of the expected value or the worst case risk measure.…”
Section: Remark 19mentioning
confidence: 99%
“…The limiting cases γ = 0 and γ = ∞ are defined as [13]. In a continuous time framework, under a filtration for which all martingales are continuous, it is shown that the only law invariant, time consistent, dynamic coherent risk measure (a dynamic convex risk measure, which additionally satisfies ρ t (λX) = λρ t (X) for all λ ∈ (L ∞ t ) + ) is either the negative of the expected value or the worst case risk measure.…”
Section: Remark 19mentioning
confidence: 99%
“…These examples all belong to the class of law-invariant convex risk measures. The failure of dynamic consistency for law-invariant coherent risk measures has already been pointed out by Delbaen [9]. Example 3.4 (Shortfall risk) Let : R → R be convex, increasing, and nonconstant and take x in the interior of (R).…”
Section: Examples and Counterexamplesmentioning
confidence: 95%
“…Moreover, since the level sets {dQ/dP | H(Q|P) ≤ c} are weakly compact (this follows, e.g., by combining Theorem 1.2 with the straightforward fact that the entropic monetary utility functional (2.1) is continuous from below), also γ must have weakly relatively compact level sets. In fact, one can show that the level sets of γ are weakly closed (see DELBAEN [2006] for the coherent and HERNÁNDEZ-HERNÁNDEZ and SCHIED [2007a, Lemma 4.1] for the general case), so that γ is the minimal penalty function of φ, and φ is continuous from below. In particular, φ and γ satisfy the assumptions of Sections 4 and 7.…”
Section: Duality Techniques In Incomplete Marketsmentioning
confidence: 99%